The Molecular Chaperone HSP90 Promotes Notch Signaling in the Germline of Caenorhabditis elegans. Issue 5 (1st May 2018) - Lissemore, James L; Connors, Elyse; Liu, Ying; Qiao, Li; Yang, Bing; Edgley, Mark L; Flibotte, Stephane; Taylor, Jon; Au, Vinci; Moerman, Donald G; Maine, Eleanor M
Abstract: In a genetic screen to identify genes that promote GLP-1 /Notch signaling in Caenorhabditis elegans germline stem cells, we found a single mutation, om40, defining a gene called ego-3 . ego-3 (om40 ) causes several defects in the soma and the germline, including paralysis during larval development, sterility, delayed proliferation of germline stem cells, and ectopic germline stem cell proliferation. Whole genome sequencing identified om40 as an allele of hsp-90, previously known as daf-21, which encodes the C. elegans ortholog of the cytosolic form of HSP90. This protein is a molecular chaperone with a central position in the protein homeostasis network, which is responsible for proper folding, structural maintenance, and degradation of proteins. In addition to its essential role in cellular function, HSP90 plays an important role in stem cell maintenance and renewal. Complementation analysis using a deletion allele of hsp-90 confirmed that ego-3 is the same gene. hsp-90 (om40 ) is an I→N conservative missense mutation of a highly conserved residue in the middle domain of HSP-90 . RNA interference-mediated knockdown of hsp-90 expression partially phenocopied hsp-90 (om40 ), confirming the loss-of-function nature of hsp-90 (om40 ) . Furthermore, reduced HSP-90 activity enhanced the effect of reduced function of both the GLP-1 receptor and the downstream LAG-1 transcription factor. Taken together, our results provide the first experimental evidence of an essential role for HSP90 in Notch signaling in development.